DIGITAL TRANSFORMATION OF BUSINESS ENTITIES UNDER THE CURRENT CONDITIONS : REALITY OR UTOPIA? (EU and comparative law issues and challenges series (ECLIC), 2020)
In recent years, the topic of penetration of information and communication technologies (ICT) in every sphere of our functioning has been resonating in our society, not excluding the business sector. The topic of digitisation and digital transformation of business entities is highly topical. This is evidenced by a rapid increase of the so-called start-ups as well as business entities that are changing the way of their production, distribution, communication and also their focus of activity to innovate both outwardly and inwardly and compete with other entities in the EU single market. In practice, this is not so simple, and transforming businesses face many obstacles that need to be removed. The penetration of ICT into the business sphere creates a single market that has a digital attribute, putting entrepreneurship and commerce into a completely different dimension. The aim of this paper is to point out the constantly evolving technologies and systems that are changing the business. In the article we will also point out the problematic areas of digital transformation of business entities and possible ways of simplifying the transformation process. Finally, we answer the question of whether the digital transformation of business in the current conditions is a reality or a utopia.